Requirements for the Digitalization of Public Institutions and Administrations and Their Role in Modernizing Administrative Activity and Achieving Good Governance (Journal of Informatics Education and Research, 2026)
The use of modern technologies in the management of public administrations and institutions has intensified since the beginning of the current century, particularly the introduction of digitalization as a tool for modernization and administrative reform in line with the global changes taking place. This research paper aims to highlight the concepts related to digitalization, its objectives and requirements, while shedding light on its positive impacts on improving administrative performance, bringing public administration closer to citizens, and enhancing transparency and good governance.